KELAYAKAN EMPIRIS PADA PENGEMBANGAN WEBLOG MATERI PENCEMARAN LINGKUNGAN UNTUK MELATIH BERPIKIR KRITIS SISWA KELAS X - MURTYNINGSIH, ARIANI (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2014)
Variations learning media is necessary, particularly with regard to technology developed at this time. Weblog as a medium that can be developed to deliver the message in the learning. Environmental pollution materials deemed appropriate for the development of this medium, because the material requires solving the problem directly in addressing environmental pollution. This study aims to describe the feasibility of the theoretical and empirical weblog based assessment and student worksheets that do student responses. This study was performed using ASSURE development model. The results showed that the media weblogs are developed based on adherence to the critical thinking of students expressed very feasible with the results of the study by 86% and the positive response of students was 92.1% of the weblog medium is developed. Keywords: weblog, critical thinking, ASSURE, environmental pollution